Invertebrate zoology a tree of life approach - Schierwater, B. (Bernd) 1958-; DeSalle, Rob (Boca Raton, FL CRC Press, an imprint of the Taylor & Francis Group, 2022)
"This book presents a comprehensive overview of invertebrate organismal zoology (IZ), defining invertebrates as any multicellular organism without a backbone (excluding plants and Fungi). While there are many IZ textbooks on the market, few combine the classical anatomical information with the newer genome level DNA sequence data and evo-devo data for teaching purposes. This book documents the latest research in these areas and combines it with classical information, giving students a unique opportunity to learn the biology of these organisms."--Provided by publisher.
Chapter 1 Invertebrates and Information p. 9 -- Chapter 2 The Basics of Phylogenetics p. 27 -- Chapter 3 Invertebrate Phylogenomics p. 45 -- Chapter 4 Modern Invertebrate Systematics p. 65 -- Chapter 5 Organizing Invertebrates p. 81 -- Higher Taxa 1 Introduction to the Invertebrate Tree of Life -- Chapter 6 The Closest Unicellular Relatives of Animals p. 95 -- Chapter 7 Phylum Placozoa p. 107 -- Chapter 8 Phylum Porifera p. 121 -- Chapter 9 Phylum Ctenophora p. 137 -- Higher Taxon 2 Cnidaria -- Chapter 10 Phylum Cnidaria: Classes Scyphozoa, Cubozoa, and Staurozoa p. 149 -- Chapter 11 Phylum Cnidaria: Class Anthozoa p. 173 -- Chapter 12 Phylum Cnidaria: Class Hydrozoa p. 193 -- Chapter 13 Phylum Cnidaria: Lineage Myxozoa p. 205 -- Higher Taxon 3 Bilateria -- Chapter 14 Phylum Platyhelminthes p. 219 -- Chapter 15 Phylum Chaetognatha p. 231 -- Chapter 16 Phylum Gastrotricha p. 253 -- Chapter 17 Phylum Rotifera p. 265 -- Chapter 18 Phyla Gnathostomulida, Micrognathozoa, and Cycliophora p. 279 -- Higher Taxon 4 Lophotrochozoa -- Chapter 19 Phylum Mollusca p. 301 -- Chapter 20 Phylum Annelida p. 311 -- Chapter 21 Phylum Brachiopoda p. 329 -- Chapter 22 Phyla Ectoprocta and Phoronida p. 341 -- Chapter 23 Phylum Nemertea p. 357 -- Chapter 24 Phylum Acanthocephala p. 369 -- Chapter 25 Phylum Entoprocta p. 379 -- Higher Taxa 5 Ecdysozoa and Arthropoda -- Chapter 26 Subphylum Crustacea p. 393 -- Chapter 27 Subphylum Hexapoda p. 407 -- Chapter 28 Phylum Arthropoda p. 423 -- Chapter 29 Subphylum Myriapoda p. 443 -- Chapter 30 Phylum Onychophora p. 459 -- Chapter 31 Phylum Nematoda p. 477 -- Chapter 32 Tardigrada p. 499 -- Chapter 33 Minor Ecdysozoan Phyla Nematomorpha, Priapulida, Kinorhyncha, Loricifera p. 513 -- Chapter 34 Phylum Xenoturbellida p. 521 -- Higher Taxon 6 Deuterostomia -- Chapter 35 Phylum Echinodermata p. 533 -- Chapter 36 Phylum Hemichordata p. 563 -- Chapter 37 Phylum Chordata p. 575.
"A Garland Science book"
Includes bibliographical references and index.
Keywords: Invertebrates; Invertebrates -- Anatomy; Invertebrates -- Morphology; Invertebrates -- Classification